2018
DOI: 10.1002/anie.201808388
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Reductive [5+1] Cycloaddition of 3‐Acetoxy‐1,4‐enynes with CO: Access to Phenols Enabled by Hydrosilanes

Abstract: A new palladium-catalyzed reductive [5+1] cycloaddition of 3-acetoxy-1,4-enynes with CO, enabled by hydrosilanes, has been developed for delivering valuable functionalized phenols. This methodology employs hydrosilanes as the external reagent to facilitate the [5+1] carbonylative benzannulation. The reaction is a conceptually and mechanistically novel carbonylative cycloaddition route for the construction of substituted phenols, through the formation of four new chemical bonds, with excellent functional-group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 71 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…We found that the reaction was not affected by a radical scavenger, such as BHT and ethyl 2-((phenylsulfonyl)­methyl)­acrylate (eq 6), implying that the reaction does not involve a radical process. The synthetic potential of the resulting product 3ba was probed (eqs 7 and 8) . Esterification of 3ba with acetic anhydride worked smoothly and afforded 4ba with a slight erosion of the enantioselectivity, attributed to the basic conditions (eq 7) .…”
mentioning
confidence: 74%
“…We found that the reaction was not affected by a radical scavenger, such as BHT and ethyl 2-((phenylsulfonyl)­methyl)­acrylate (eq 6), implying that the reaction does not involve a radical process. The synthetic potential of the resulting product 3ba was probed (eqs 7 and 8) . Esterification of 3ba with acetic anhydride worked smoothly and afforded 4ba with a slight erosion of the enantioselectivity, attributed to the basic conditions (eq 7) .…”
mentioning
confidence: 74%
“…The carbonylation process comprises one of the most fundamental and promising tactics for building up the privileged carbonyl-containing organic molecules and derivatives, which has greatly benefited both academia and industry application . Meanwhile, CO gas as the most direct C1 source in organic syntheses has been extensively exploited for over a half century, especially with respect to the transition-metal catalyzed version, and has gained remarkable achievements, even benefiting the total synthesis of a myriad of natural products . Notwithstanding its robustness, this conversion still encounters several non-negligible restraints such as a difficult system (toxicity, flammability, and high pressure) as well as aspects affecting reaction efficacy (poison metal catalyst) .…”
mentioning
confidence: 99%
“…T ransition-metal (TM)-catalyzed carbonylation reaction [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , especially palladium-catalyzed tandem Heck/carbonylation reaction, presents an efficient method to construct a variety of synthetically versatile carbonyl compounds from readily accessible organic halides and alkenes [17][18][19][20][21] . Moreover, these methods have been applied as key steps in the total synthesis of natural products and bioactive molecules [22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%